APLIKASI SISTEM INFORMASI MOBILE AKADEMIK - Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Wireless technology can be exploited its potential to use mobile technology to use sms applications to meet the demand of value which can be accessed by the parent guardian of any. The purpose of this study to apply the software on academic information system for the secondary school level as an effective delivery of information for high school students. Computer software for mobile information system academic is using windows-based programming language is Visual Basic 6. With the design of mobile information systems can facilitate the delivery of academic information for the parents. Keywords: Academic Mobile